2012
DOI: 10.1094/pdis-03-11-0156-re
|View full text |Cite
|
Sign up to set email alerts
|

Recent Genotypes of Phytophthora infestans in the Eastern United States Reveal Clonal Populations and Reappearance of Mefenoxam Sensitivity

Abstract: Isolates of Phytophthora infestans (n = 178) were collected in 2002 to 2009 from the eastern United States, Midwestern United States, and eastern Canada. Multilocus genotypes were defined using allozyme genotyping, and DNA fingerprinting with the RG-57 probe. Several previously described and three new mulitilocus genotypes were detected. The US-8 genotype was found commonly on commercial potato crops but not on tomato. US-20 was found on tomato in North Carolina from 2002 through 2007 and in Florida in 2005. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 40 publications
4
84
0
5
Order By: Relevance
“…However, the level of HR observed between I2 and AVR3a KI was relatively weak therefore we cannot rule out that other effectors present in this P. infestans determine the observed I2-mediate resistance. Most late blight lineages infect both potato and tomato (Goodwin, Smart et al 1998), although some lineages primarily infect tomato and are not likely to cause disease on potato plants in the field (Hu, Perez et al 2012 identified in this study gives partial resistance to P. infestans strains carrying either of the AVR3a variants in the transient assays used (Fig. 7).…”
Section: Discussionmentioning
confidence: 60%
“…However, the level of HR observed between I2 and AVR3a KI was relatively weak therefore we cannot rule out that other effectors present in this P. infestans determine the observed I2-mediate resistance. Most late blight lineages infect both potato and tomato (Goodwin, Smart et al 1998), although some lineages primarily infect tomato and are not likely to cause disease on potato plants in the field (Hu, Perez et al 2012 identified in this study gives partial resistance to P. infestans strains carrying either of the AVR3a variants in the transient assays used (Fig. 7).…”
Section: Discussionmentioning
confidence: 60%
“…Because widely used site-specific fungicides, such as mefenoxam (the active isomer in metalaxyl), inhibit sporulation and mycelial growth inside host tissues by specifically inhibiting RNA polymearase-1, a mutation that changes the affinity of target sites could easily lead to fungicide resistance (Davidse et al 1983). Significant variations for mefenoxam sensitivity were identified among P. infestans isolates from the different genotypes (Hu et al 2012;Danies et al 2013;Fry et al 2013;Kalischuk et al 2012). Isolates of the US-8 and US-11 genotypes were resistant to mefenoxam, while isolates of the genotypes US-22, US-23 and US-24 were initially highly sensitive to sensitive to this fungicide.…”
Section: Evolution Of Late Blight Populations In United States and Camentioning
confidence: 98%
“…For example, from 2002 to 2007, the P. infestans genotypes US-20 and US-21 were the predominant genotypes affecting tomatoes in North Carolina and Florida (Hu et al 2012). However, inoculum distribution enabled the US-22 genotype (mating type A2) to rapidly displace the other genotypes and cause significant damage to tomato and potato growing areas in the northeastern United States and central Canada (Hu et al 2012;Kalischuk et al 2012).…”
Section: Evolution Of Late Blight Populations In United States and Camentioning
confidence: 99%
See 2 more Smart Citations